Models, Methods and Tools for Product Service Design The Manutelligence Project - Cattaneo, Laura; Terzi, Sergio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Chapter 4 is available open access under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License via link.springer.com.
Introduction -- Engineering and business requirements definition, analysis and validation -- Life cycle Management for Product-Service Systems -- A Platform for Product-Service Design and Manufacturing Intelligence -- Tools and procedures to embed and retrieve Product-Service lifecycle knowledge -- Life Cycle Assessment and Life Cycle Costing for PSS -- Use cases -- Business Exploitation.
Keywords: Manufactures; Computational intelligence; Artificial intelligence; Service industries; Machines, Tools, Processes; Computational Intelligence; Artificial Intelligence; Services